Haematological changes in Bufo maculatus treated with sublethal concentrations of Cadmium - Lawrence Ikechukwu Ezemonye; Alex Ajeh Enuneku (MDPI AG, 2011)
Adult Bufo maculatus was exposed to sublethal cadmium concentrations of 0.25, 0.50, 1.00 and 2.00 mg/L. The toxicant from which the cadmium concentrations were prepared was cadmium chloride (CdCl2.H2O). There were three replicate tanks per treatment and three individuals per tank including control groups. The hematologic alterations based on the examination of blood indices during the 28 days of exposure showed that total erythrocyte count (TEC), hematocrit (Hct) and hemoglobin (Hb) concentration decreased (P<0.05) relative to controls. The decline was concentration- dependent as concentration of cadmium increased. The decline in hemoglobin and hematocrit in the experimental organism could be due to a decrease in the synthesis or release of erythrocytes into the circulation or an increase in the rate of erythrocyte destruction inflicted by cadmium toxicity. There was significant (P<0.05) elevation in total leuko- leukocyte count (TLC) with increase in the concen- cyte concentration of cadmium. The increase in total leukocyte count observed in this study could be attributed to a stimulation of the immune system in response to tissue damage caused by cadmium toxicity. The study has shown that the exposure of the Bufo maculatus toad to cadmium can inflict alterations in the hematologic indices, which could induce unfavorable physiological changes in the amphibian, which may lead to death. There is, therefore, the need to protect amphibians in order to sustain the biodiversity in the Nigerian Niger Delta ecological zone.